Temporal Variability of Soil Carbon and Nitrogen in Cotton Production on the Texas High Plains. (1st June 2019) - Burke, J.A.; Lewis, K.L.; Ritchie, G.L.; Moore‐Kucera, J.; DeLaune, P.B.; Keeling, J.W.
Abstract : Soil organic carbon (SOC) is a key indicator of soil health as it is important in essential soil functions related to nutrient cycling and soil productivity. Although, it can take several decades to increase SOC in semi‐arid ecoregions, it is possible that the low organic matter background in sandy soils typical of semi‐arid soils may show greater fluctuations compared to soils from other regions. This study was conducted to evaluate the temporal C and N dynamics of cotton ( Gossypium hirsutum L.) cropping systems in a semi‐arid region. The effects of no‐tillage (NT) and cover crop use on SOC, potassium permanganate oxidizable carbon (POXC), inorganic nitrogen (Ninorg ), and microbial respiration were investigated in a long‐term study (∼19 yr) at Lamesa, TX, comparing conventional tillage (CT), winter fallow, to no‐tillage rye cover (R‐NT), and no‐tillage mixed species cover (M‐NT) on an Amarillo fine sandy loam. Results showed SOC and POXC were greatest during periods of active cover crop and cotton root growth. Soil organic C and POXC were significantly correlated ( R 2 = 0.75; p < 0.0001), but poorly correlated to microbial respiration ( R 2 = 0.41, p = 0.0001; and R 2 = 0.02, p = 0.8781, respectively). Conservation management practices did not impact Ninorg . Soil organic C and POXC levels were more variable than previously reported and responded to active root growth in this semi‐arid, sandy soil. Core Ideas Soil organic C and K permanganate oxidizable C were more temporally variable than previously reported. Soil organic C and K permanganate oxidizable C were greatest during active cover than fallow periods. Long‐term conservation management did not significantly increase inorganic N.